Ostreolysin induces browning of adipocytes and ameliorates hepatic steatosis. Issue 12 (15th May 2018) - Nimri, Lili; Staikin, Katerina; Peri, Irena; Yehuda‐Shnaidman, Einav; Schwartz, Betty
Abstract: Background and Aim: Non‐alcoholic fatty liver disease (NAFLD) is associated with all features of the metabolic syndrome. Deposition of excess triglycerides in liver cells, a hallmark of NAFLD, is associated with loss of insulin sensitivity. Ostreolysin (Oly) is a 15‐kDa fungal protein known to interact with cholesterol‐enriched raft‐like membrane domains. We aim to test whether a recombinant version of Oly (rOly) can induce functional changes in vitro in adipocytes or in vivo in mice fed a high‐fat diet (HFD). Methods: White preadipocyte 3T3‐L1 cells or mouse primary adipocytes treated with rOly. Male C57BL/6 mice were fed a control or HFD and treated with saline or with rOly (1 mg/kg BW) every other day for 4 weeks. Results: White preadipocyte 3T3‐L1 cells or mouse primary adipocytes treated with rOly acquire a browning phenotype through activation of 5′ adenosine monophosphate‐activated protein kinase and downregulation of tumor necrosis factor α‐mediated activation of IκB kinase ε and TANK‐binding kinase 1. HFD‐fed mice treated with rOly showed a 10% reduction in BW and improved glucose tolerance, which paralleled improved expression of liver and adipose functionality, metabolism, and inflammation status, mimicking the in vitro findings. Conclusion: This study provides first evidence of rOly's prevention of HFD‐induced NAFLD by stimulating liver and adipose muscle tissue functionality and oxidative potential, improving glucose tolerance, and ameliorating the metabolic profile of diet‐induced obese mice.